Multilateral Foreign Aid, Bilateral Foreign Aid, and Foreign Direct Investment in Latin America - Quazi, Rahim M.; Ballentine, Wayne E.; Bindu, Farzana; Blyden, Lois (International Journal of Economics and Financial Issues, 2019)
This study analyzes the impact of foreign aid on foreign direct investment (FDI) in Latin America. Using the Feasible Generalized Least Squares panel estimation methodology with 1996-2017 panel data from 19 countries, this study finds that the impact of foreign aid on FDI in Latin America is insignificant. However, when total aid is disaggregated into bilateral aid and multilateral aid, it is found that multilateral aid significantly boosts FDI, but bilateral aid does not. These results lend credence to the hypothesis that multilateral aid (which is likely to be aligned with the non-political developmental orientation of the multilateral donor organizations) is channeled into legitimate development projects that raise the productivity of capital, which helps attract more FDI to the recipient countries. However, bilateral aid (which is often dictated by the geo-political strategic self-interests of the donor countries) can get funneled into non-productive projects. The study also finds that the other significant drivers of FDI in the sample countries include economic freedom, quality of governance, market size, rate of return, infrastructure, and human capital. These results appear robust across several model specifications. Keywords: Foreign aid, foreign direct investment, Latin America JEL Classifications: F35, F21 DOI: https://doi.org/10.32479/ijefi.7520